Personal Branding Anggota DPR dalam Sidang Pengesahan UU TNI: Strategi Komunikasi Politik dan Representasi Diri di Ruang Publik - Putri Ekaresty Haes; Sugeng Karyadi; Yunidyawati Azlina; Imam Jayanto; Musran Munizu (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2025)
This study aims to analyze the forms of personal branding exhibited by members of the Indonesian House of Representatives (DPR) during the legislative session for the ratification of the Indonesian National Armed Forces (TNI) Law. Employing a qualitative–interpretative approach with Fairclough’s Critical Discourse Analysis (CDA) as the method, this research explores the political communication strategies employed by DPR members in constructing their public persona through physical appearance, rhetorical style, and personal narratives communicated to the public and media. The primary data source is a news article titled “7 Statements from DPR RI Commission I Regarding the Revision of the TNI Law, Revealing the Discussed Articles” by Devira Prastiwi, published on Liputan6.com and updated on March 16, 2025. The findings indicate that several DPR members actively used the parliamentary session as a stage to build their brand, projecting traits such as nationalism, courage, integrity, and concern for military and defense issues. These personal branding strategies not only reflect their political positioning but also aim to strengthen emotional connections with constituents and broaden their electoral reach. This research contributes to the understanding of the dynamics of political personalization in the mediatized era, where personal image becomes a crucial instrument in shaping public perception of legislative performance.